Breast motion asymmetry during running - Mills, C.; Risius, D.; Scurr, J. (Journal of Sports Sciences, 2015)
Breast asymmetry is common in females, despite a similar driving force; dynamic activity may result in asymmetrical breast motion. This preliminary study investigated how breast categorisation (left/right or dominant/non-dominant) may affect breast support recommendations and its relationship with breast pain. Ten females ran on a treadmill at 10 kph in three breast supports (no bra, everyday bra, sports bra). Five reflective markers on the thorax and nipples were tracked using infrared cameras (200 Hz) during five running gait cycles in each breast support. Multiplanar displacements of both breasts were calculated relative to the thorax. Although the maximum individual participant difference was 2.4 cm (mediolaterally) between the left and right breast, no left/right differences were found in any direction or support condition. Notably, correlations between breast pain and anterioposterior breast displacement were stronger with the left breast (r = 0.614) and moderate with the right breast (r = 0.456). Following participant categorisation according to the greatest magnitude of superioinferior breast displacement (dominant breast), results showed significant differences in displacement for all directions across different breast supports. When using breast kinematic data to examine relationships with breast pain or to recommend breast support requirements, data on both breasts should be collected.